High altitude dilemmas: assessing academic air travel reduction measures by comparing reduction potential and willingness - Rocco Bagutti; Ariane Wenger; Peter Ranacher (Environmental Research Communications)
Many researchers consider air travel crucial for a successful career and fly frequently to attend conferences, participate in meetings, teach classes, and conduct fieldwork, which creates significant greenhouse gas (GHG) emissions that often account for the largest share of a university’s emission total. Several universities have attempted to address this issue by implementing measures to reduce GHG emissions from academic air travel. Ideally, these measures are both effective in reducing emissions and acceptable to the academic staff willing to endorse them. We evaluated five air travel reduction measures and compared their GHG emission reduction potential to academics’ willingness to implement them. We calculated reduction potentials based on empirical flight data from the University of Zurich’s Department of Geography and conducted an online survey among the department’s academic staff to assess willingness. On average, academic staff were willing to implement all five measures. Measures restricting travel showed the highest reduction potential but the lowest willingness to adopt among academic staff. Conversely, measures involving the transition to alternative travel modes showed higher willingness but lower reduction potentials. Our results suggest that there is no straightforward answer for universities aiming to reduce their air travel emissions. In addition to implementing more acceptable low-impact measures, universities must explore examples of good practices and endeavor to remove obstacles to high-impact measure implementation.